Invasão ao Iraque: um estudo das coberturas das revistas Veja e Carta Capital - Val, Helena Santeiro do (2007)
This dissertation has as object of study the north-american invasion to Irak and the covering of the theme by the magazines of national circulation Veja and Carta Capital, from january of 2003 to february of 2005, with the use of a table to classify the news d transcription of the texts. The present work pretends to show the relevance of the invasion to the political sciences, analyse the transmission of information in Brazil through its midia, and distinguish the world visions of the analysed means. This project will inquirer if there is a positioning of the studieds magazines, wich are they and debate the possibilities of influency in the reader comprehension. From the invasion of Irak we can also understand the role of potency of United States in the world today, wich is reconfiguring the global order